Sonohysterography in infertility patients - Hilario, Roly (2015)
Introduction: Congenital anomalies and acquired diseases of the uterus have been obstacles for successful treatment of infertility. The uterine cavity is where the embryo normally implants. It is important a proper evaluation of the uterine cavity to rule out or detect changes that may affect implantation. Hysterosonography is a diagnostic method used in the evaluation of the uterine cavity. The most common indication for sonohysterography in patients with infertility is suspected intrauterine pathology. Objectives: To describe routine sonohysterography findings in an infertile population, with or without suspicion of endometrial pathology, in relation to patient’s age. Design: Descriptive retrospective study. Setting: Clínica Procrear, Lima, Peru. Participants: Women in evaluation for infertility. Methods: Between January and April 2013 hysterosonography was performed in 305 patients as part of infertility study. SPSS 15 program was used for analysis. Main outcome measures: Findings in the uterine cavity. Results: Average age of patients was 36 years. Endometrial cavity abnormal findings was found in 25.4% (77/305) of cases; most common findings were endometrial polyps in 50 (16.4%), uterine synechiae in 9 (3%), submucosal fibroids in 6 (2%) and other pathology in 12 cases. The age group presenting more intrauterine pathology was the 31-40 years group (29%) and the age group with less pathology was the 18-30 years group (13%). Conclusions: Hysterosonography is a procedure that should be performed in all patients with infertility because it improves uterine cavity evaluation, thereby preventing implantation failure and allowing endocervical permeability.